ENHANCING THE ABILITY OF CLASSROOM TEACHERS IN IMPLEMENTING THE LEARNING USING MEDIA INTERACTIVE CD-BASED INTEGRATED SCIENCE EDUTAINMENT THROUGH THE IMPLEMENTATION OF SUPERVISION WITH THE TECHNIQUE OF DEMONSTRATION TEACHING IN SDN MEDOKAN AYU I/270 SURABAYA - Enniek Dwi Nurhayati (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
The presence of the media is essential in teaching and learning. In the process of unclearness of the material presented, you can help by introducing the media as an intermediary. The complexity of the material presented can be simplified with the help of media. The media can present what the teacher cannot express with certain words or sentences. Even material abundance can be concretized by the presence of mass media. Thus, it is easier for students to assimilate the materials than without the help of the media. The authors would like to perform School Action Research at SDN Medokan Ayu I/270 Surabaya with the title "Improving the Ability of Homeroom Teachers in Implementing Learning Using Flash CD Animation Media through the Implementation of Supervision with Demonstration Teaching Techniques." ".This is a school action research project that will be carried out in two (two) cycles. Each cycle has four stages: 1) action planning, 2) action implementation, 3) action observation and interpretation, analysis and assessment, and 4) reflection. Ten homeroom teachers and two teachers from SDN Medokan Ayu I/270 Surabaya participated in this study. At SDN Medokan Ayu I/270 Surabaya, supervision with demonstration teaching strategies can be used to improve classroom teachers' ability to execute learning by using Integrated Science Edutainment Interactive CD-Based media.